2008
DOI: 10.3382/ps.2007-00229
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Calcium and Phytate in Broiler Diets. 2. Effects on Total and Soluble Phosphorus Excretion

Abstract: Dietary Ca has been reported to influence the amount of phytate excreted from broilers and affect the solubility of P in excreta. To address the effects of dietary Ca and phytate on P excretion, 12 dietary treatments were fed to broilers from 16 to 21 d of age. Treatments consisted of 3 levels of phytate P (0.10, 0.24, and 0.28%) and 4 levels of Ca (0.47, 0.70, 0.93, and 1.16%) in a randomized complete block design. Feed phytate concentrations were varied by formulating diets with 3 different soybean meals (SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Our results are in agreement with those of He et al (2007) and Leytem et al (2008b), who characterized P compounds in poultry and dairy manures by solution 31 P-NMR in NaOH + EDTA extracts. They found that in dairy manure, inorganic P was the major P fraction (64-73 %), followed by 6 % phytic acid, 14 to 22 % other monoesters, and 7 % phosphodiesters, whereas in the poultry manure, results showed that orthophosphate accounted for 51 to 63 %, phytic acid 24 to 33 %, other phosphomonoesters 6 to 12 %, and phospholipids and DNA 2 % each.…”
Section: Resultssupporting
confidence: 92%
“…Our results are in agreement with those of He et al (2007) and Leytem et al (2008b), who characterized P compounds in poultry and dairy manures by solution 31 P-NMR in NaOH + EDTA extracts. They found that in dairy manure, inorganic P was the major P fraction (64-73 %), followed by 6 % phytic acid, 14 to 22 % other monoesters, and 7 % phosphodiesters, whereas in the poultry manure, results showed that orthophosphate accounted for 51 to 63 %, phytic acid 24 to 33 %, other phosphomonoesters 6 to 12 %, and phospholipids and DNA 2 % each.…”
Section: Resultssupporting
confidence: 92%
“…This finding suggested that solubility of P in manures could be altered by microbial degradation of organic P fractions. The WSP content and the ratio of WSP:total P was also shown to be affected by the P composition of broiler litter (Leytem and Maguire, 2006). Leytem et al, (2008) subsequently showed that WSP in litter was strongly influenced by the phytate P content in litter, with steep linear reductions in WSP (as phytate P content) relative to total P in the litter increased.…”
Section: Resultsmentioning
confidence: 95%
“…The WSP content and the ratio of WSP:total P was also shown to be affected by the P composition of broiler litter (Leytem and Maguire, 2006). Leytem et al, (2008) subsequently showed that WSP in litter was strongly influenced by the phytate P content in litter, with steep linear reductions in WSP (as phytate P content) relative to total P in the litter increased. Therefore, dietary and other factors that alter the amount of phytate P excreted in the manure alter the solubility of the P therein.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, Leytem et al (2006) found that concentrations of water soluble (extractable) P and phytate-P, as proportions of total P in poultry excreta, are linearly related (r 2 = 0.94) in poultry excreta and both dietary Ca levels and Ca:available P ratios are critical to the water soluble P content of broiler litter (Leytem et al, 2007a). Subsequently, Leytem et al (2007b) reported that reducing phytate levels in broiler diets from 2.8 to 1.0 g kg − 1 with low-phytate soybean meal reduced total P (62.7%), water soluble P (66.4%) and phytate-P (74.6%) in excreta by broadly similar magnitudes. Also, increasing dietary Ca from 4.7 to 11.6 g kg − 1 increased the amount of phytate-P (43.0%) excreted but decreased the output of water soluble P (57.0%).…”
Section: Calcium Phytate Phytase and Excreta Qualitymentioning
confidence: 96%